A review on Lactococcus lactis: from food to factory - Song, Adelene Ai‑Lian; Lionel, L. A. In; Swee, Hua Erin Lim; Abdul Rahim, Raha (BioMed Central, 2017)
Lactococcus lactis has progressed a long way since its discovery and initial use in dairy product fermentation, to its present biotechnological applications in genetic engineering for the production of various recombinant proteins and metabolites that transcends the heterologous species barrier. Key desirable features of this gram-positive lactic acid non-colonizing gut bacteria include its generally recognized as safe (GRAS) status, probiotic properties, the absence of inclusion bodies and endotoxins, surface display and extracellular secretion technology, and a diverse selection of cloning and inducible expression vectors. This have made L. lactis a desirable and promising host on par with other well established model bacterial or yeast systems such as Escherichia coli, Salmonella cerevisiae and Bacillus subtilis. In this article, we review recent technological advancements, challenges, future prospects and current diversified examples on the use of L. lactis as a microbial cell factory. Additionally, we will also highlight latest medical-based applications involving whole-cell L. lactis as a live delivery vector for the administration of therapeutics against both communicable and non-communicable diseases.